PENGARUH MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA BAGIAN UMUM SETDA KABUPATEN PANDEGLANG - Hepi Rostikariani Hepi Rostikariani (NIAGARA Scientific Journal, 2016)
Based on the results of the author's observations during the pre-survey at the General Section of the Regional Secretariat of Pandeglang Regency, there are symptoms which illustrate that it is suspected that the performance of employees at the General Section of the Regional Secretariat of Pandeglang Regency is suspected. This is presumably due to the influence of work motivation factors. The purpose of this study was to determine the effect of work motivation on employee performance at the General Section of Regional Secretariat of Pandeglang Regency. The research method used in this study is a quantitative descriptive analysis method that tries to describe the condition of work motivation in its effect on employee performance in the General Section of Regional Secretariat of Pandeglang Regency. The results showed that 0.187 or 18.7% of employee performance was influenced by work motivation.